2017
DOI: 10.1103/physrevc.96.064606
|View full text |Cite
|
Sign up to set email alerts
|

Examination of evidence for collinear cluster tri-partition

Abstract: In a series of the experiments at different time-of-flight spectrometers of heavy ions we have observed manifestations of a new at least ternary decay channel of low excited heavy nuclei. Due to specific features of the effect, it was called collinear cluster tri-partition (CCT). The experimental results obtained initiated a number of theoretical articles dedicated to different aspects of the CCT. We compare theoretical predictions with our experimental data, only partially published so far. The model of one o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
3
7
0
Order By: Relevance
“…The experimental findings and model analysis indicate that the true quaternary decay of the 252 Cf(sf) goes via very elongated prescission configurations of the mother nucleus. Similar conclusion was drawn in [7] concerning the mechanism of the collinear cluster tri-partition (CCT) of the same nucleus. Presumably the quaternary decay is due to preformation in the valley of the symmetric nuclear shapes of the potential energy surface of 252 Cf specific nuclear shape which looks like a deformed magic core (strong shell minima at N ≈ 88, 100 and Z ≈ 60) and two light clusters on the sides.…”
Section: Resultssupporting
confidence: 74%
“…The experimental findings and model analysis indicate that the true quaternary decay of the 252 Cf(sf) goes via very elongated prescission configurations of the mother nucleus. Similar conclusion was drawn in [7] concerning the mechanism of the collinear cluster tri-partition (CCT) of the same nucleus. Presumably the quaternary decay is due to preformation in the valley of the symmetric nuclear shapes of the potential energy surface of 252 Cf specific nuclear shape which looks like a deformed magic core (strong shell minima at N ≈ 88, 100 and Z ≈ 60) and two light clusters on the sides.…”
Section: Resultssupporting
confidence: 74%
“…Later, due to the second rupture, the light cluster and the light FF become free. In general, the kinematics of the process seems to be similar to that discussed in [7].…”
Section: Discussionsupporting
confidence: 58%
“…A total yield of two Ni peaks in Ex1 does not exceed 10 −4 per binary fission which agrees with our previously obtained value. The data of Ex2 indicated that the heavy clusters in the ternary prescission configurations are predominantly magic nuclei (Table 1 in [7]). Noticeably large statistics in Ex1 allowed us to confirm previous observation.…”
Section: Experimental and Resultsmentioning
confidence: 98%
“…Solyakin et al proposed the collinear mode of tripartition [12], when searching for TTF of 238 U by 1-GeV protons. This concept was most successfully realized in JINR experiments on FOBOS and mini-FOBOS setups [13,14,15]. All the results presented below are obtained within the framework of the "missing-mass" approach.…”
Section: Introductionmentioning
confidence: 98%